Patterns of gene expression in ovaries of sexual vs. asexual lineages of a freshwater snail - McElroy, Kyle E.; Bankers, Laura; Soper, Deanna; Hehman, Gery; Boore, Jeffrey L.; Logsdon, John M.; Neiman, Maurine (Frontiers in Ecology and Evolution, 2022)
Why sexual reproduction is so common when asexual reproduction should be much more efficient and less costly remains an open question in evolutionary biology. Comparisons between otherwise similar sexual and asexual taxa allow us to characterize the genetic architecture underlying asexuality, which can, in turn, illuminate how this reproductive mode transition occurred and the mechanisms by which it is maintained or disrupted. Here, we used transcriptome sequencing to compare patterns of ovarian gene expression between actively reproducing obligately sexual and obligately asexual females from multiple lineages of Potamopyrgus antipodarum, a freshwater New Zealand snail characterized by frequent separate transitions to asexuality and coexistence of otherwise similar sexual and asexual lineages. We also used these sequence data to evaluate whether population history accounts for variation in patterns of gene expression. We found that source population was a major source of gene expression variation, and likely more influential than reproductive mode. This outcome for these common garden-raised snails is strikingly similar to earlier results from field-collected snails. While we did not identify a likely set of candidate genes from expression profiles that could plausibly explain how transitions to asexuality occurred, we identified around 1000 genes with evidence of differential expression between sexual and asexual reproductive modes, and 21 genes that appear to exhibit consistent expression differences between sexuals and asexuals across genetic backgrounds. This second smaller set of genes provides a good starting point for further exploration regarding a potential role in the transition to asexual reproduction. These results mark the first effort to characterize the causes of asexuality in P. antipodarum, demonstrate the apparently high heritability of gene expression patterns in this species, and hint that for P. antipodarum, transitions to asexuality might not necessarily be strongly associated with broad changes in gene expression.